Reliability Analysis of pH Measurement on TLC4502 with E201C Electrodes based on ATmega328P Microcontroller: Approach to Analysis of Variation with ANOVA - James Julian; Fitri Wahyuni; Faiz Daffa Ulhaq (ELKHA : Jurnal Teknik Elektro, 2023)
The development of the water management system has so far reached the stage of utilizing IoT technology in the monitoring and operation process. An essential factor in water that affects the quality of a substance is pH. The research aims to analyze and ensure that the devices have a small pH measurement error rate with TLC4502 & E201C. The calibration process was carried out using linear regression, and  value of 0.99 was obtained. Analysis was carried out using one-way ANOVA and Tukey HSD methods, and it was found that all data pairs rejected the null hypothesis (H0) and accepted the alternate hypothesis (H1). This hypothesis indicated a significant difference in the relative measurement error of pH in each condition. The standard error value of each measurement after filtration was 0.00, with an uncertainty value ranging from 0.07 to 0.02. If the sensor can provide measurement results with low error and high accuracy, then the sensor can be widely circulated and used. Through this research, the feasibility of a measuring instrument was developed based on the perspective of errors and high accuracy. A quality measuring instrument certainly helpful in various fields from the fisheries, hydroponics, and environmental sectors.